Answer:
a square backyard with width (x - 9)
Step-by-step explanation:
x²−18x + 81 = x² - (2 x 9) x + 9² = (x - 9)²
width = area / length = (x - 9)² / (x - 9) = x - 9
Length = width
This is a square backyard
Answer:
It has a minimum and no maximum.
Step-by-step explanation:
This is the graph of a parabola that opens up, so it has a minimum but no maximum.
Answer:
![c=2\sqrt{89}](https://tex.z-dn.net/?f=c%3D2%5Csqrt%7B89%7D)
Step-by-step explanation:
Pythagorean theorem is:
![c^{2} =a^{2} +b^{2}](https://tex.z-dn.net/?f=c%5E%7B2%7D%20%3Da%5E%7B2%7D%20%2Bb%5E%7B2%7D)
![c^{2}=10^{2}+16^{2} \\c^{2} =100+256\\c^{2}=356\\c=\sqrt{356} \\c=2\sqrt{89}](https://tex.z-dn.net/?f=c%5E%7B2%7D%3D10%5E%7B2%7D%2B16%5E%7B2%7D%20%20%20%5C%5Cc%5E%7B2%7D%20%3D100%2B256%5C%5Cc%5E%7B2%7D%3D356%5C%5Cc%3D%5Csqrt%7B356%7D%20%20%5C%5Cc%3D2%5Csqrt%7B89%7D)
Answer:
The factored form of x^3 -1 will be:
![x^3-1^3=\left(x-1\right)\left(x^2+x+1\right)](https://tex.z-dn.net/?f=x%5E3-1%5E3%3D%5Cleft%28x-1%5Cright%29%5Cleft%28x%5E2%2Bx%2B1%5Cright%29)
Step-by-step explanation:
Given the expression
![x^3-1](https://tex.z-dn.net/?f=x%5E3-1)
Rewrite 1 as 1³
![=x^3-1^3](https://tex.z-dn.net/?f=%3Dx%5E3-1%5E3)
![\mathrm{Apply\:Difference\:of\:Cubes\:Formula:\:}x^3-y^3=\left(x-y\right)\left(x^2+xy+y^2\right)](https://tex.z-dn.net/?f=%5Cmathrm%7BApply%5C%3ADifference%5C%3Aof%5C%3ACubes%5C%3AFormula%3A%5C%3A%7Dx%5E3-y%5E3%3D%5Cleft%28x-y%5Cright%29%5Cleft%28x%5E2%2Bxy%2By%5E2%5Cright%29)
![x^3-1^3=\left(x-1\right)\left(x^2+x+1\right)](https://tex.z-dn.net/?f=x%5E3-1%5E3%3D%5Cleft%28x-1%5Cright%29%5Cleft%28x%5E2%2Bx%2B1%5Cright%29)
![=\left(x-1\right)\left(x^2+x+1\right)](https://tex.z-dn.net/?f=%3D%5Cleft%28x-1%5Cright%29%5Cleft%28x%5E2%2Bx%2B1%5Cright%29)
Thus, the factored form of x^3 -1 will be:
![x^3-1^3=\left(x-1\right)\left(x^2+x+1\right)](https://tex.z-dn.net/?f=x%5E3-1%5E3%3D%5Cleft%28x-1%5Cright%29%5Cleft%28x%5E2%2Bx%2B1%5Cright%29)
Answer:
6/5 or 1 1/5
Edit:
soo
= ![6\sqrt{5}](https://tex.z-dn.net/?f=6%5Csqrt%7B5%7D)
since they both are being multipled to the square root of 5, you can just add them (i think)
Step-by-step explanation:
6 times the square root of 5
you add 4 and 2